Portfolio Flows, Global Risk Aversion and Asset Prices in Emerging Markets - Ananchotikul, Nasha (IMF Working Papers; Working Paper ;, 2014)
In recent years, portfolio flows to emerging markets have become increasingly large and volatile. Using weekly portfolio fund flows data, the paper finds that their short-run dynamics are driven mostly by global 'push' factors. To what extent do these cross-border flows and global risk aversion drive asset volatility in emerging markets? We use a Dynamic Conditional Correlation (DCC) Multivariate GARCH framework to estimate the impact of portfolio flows and the VIX index on three asset prices, namely equity returns, bond yields and exchange rates, in 17 emerging economies. The analysis shows that global risk aversion has a significant impact on the volatility of asset prices, while the magnitude of that impact correlates with country characteristics, including financial openness, the exchange rate regime, as well as macroeconomic fundamentals such as inflation and the current account balance. In line with earlier literature, portfolio flows to emerging markets are also found to affect the level of asset prices, as was the case in particular during the global financial crisis.